King of spies : the dark reign of America's spymaster in Korea - Harden, Blaine (London : MANTLE, 2017)
Donald Nichols was 'a one man war', according to his US Air Force commanding general. He won the Distinguished Service Cross, along with a chest full of medals for valour and initiative in the Korean War. His commanders described Nichols as the bravest, most resourceful and effective spymaster of that forgotten war. But there is far more to Donald Nichols' story than first meets the eye. In 'King of Spies', author Blaine Harden reveals one of the most astonishing - and previously untold - spy stories of the 20th century
ntroduction: The spy who came in from the motor pool -- Part I. Most valuable spy -- Nichols of Korea -- Rhee and son -- Muzzling Mr. Nichols -- Part II. War spy -- Dark star -- Code break bully -- Any means necessary -- Empire of islands -- Famous in Pyongyang -- Part III. Ruined spy -- Sacked -- Shocked -- Adrift and accused -- Nolo contendere -- A spy's grave.
Includes bibliographical references (pages 243-249) and index.
Keywords: Nichols, Donald, -- 1923-1992.; Korean War, 1950-1953 -- Secret service -- United States; United States. -- Air force -- BIOGRAPHY; Korean War, 1950-1953 -- Atrocities; POLITICAL SCIENCE / Political Freedom & Security / Intelligence; HISTORY / Military / Korean War; BIOGRAPHY & AUTOBIOGRAPHY / Military